KAJIAN META-ANALISIS: INDIKATOR PRIORITAS RAPOR PENDIDIKAN DALAM KURIKULUM MERDEKA - Sella Fajrina Yuza; Misbahul Jannah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study was motivated by the transformation of education through the Independent Curriculum in order to respond to global challenges. The focus of the problem is to holistically synthesize six priority indicators of the Education Report Card: literacy, numeracy, character, safety climate, diversity climate, and learning quality, which are often only examined partially. Using meta-analysis, this study integrates findings from 60 scientific articles published between 2021 and 2025 through systematic searching and data documentation. The analysis shows a positive impact on education quality, despite obstacles such as low levels of higher cognitive literacy, weaknesses in numeracy reasoning, and bullying issues in the safety climate. The main conclusion confirms that although the Independent Curriculum has a significant impact, its success requires continuous efforts through Data-Based Planning (PBD), optimization of the Merdeka Mengajar Platform (PMM), and intensive collaboration between schools and parents to overcome implementation obstacles in the field. ABSTRAK Penelitian ini dilatarbelakangi oleh transformasi pendidikan melalui Kurikulum Merdeka guna menjawab tantangan global. Fokus masalahnya adalah mensintesis secara holistik enam indikator prioritas Rapor Pendidikan literasi, numerasi, karakter, iklim keamanan, iklim kebhinekaan, dan kualitas pembelajaranyang sering kali hanya dikaji secara parsial. Menggunakan metode meta-analisis, penelitian ini mengintegrasikan temuan dari 60 artikel ilmiah periode 2021-2025 melalui tahapan penelusuran sistematis dan dokumentasi data. Hasil analisis menunjukkan dampak positif pada mutu pendidikan, meski terdapat kendala seperti rendahnya literasi kognitif tingkat tinggi, kelemahan penalaran numerasi, serta isu perundungan pada iklim keamanan. Simpulan utama menegaskan bahwa meskipun Kurikulum Merdeka memberikan pengaruh signifikan, keberhasilannya memerlukan upaya berkelanjutan melalui Perencanaan Berbasis Data (PBD), optimalisasi Platform Merdeka Mengajar (PMM), dan kolaborasi intensif antara sekolah dengan orang tua untuk mengatasi hambatan implementasi di lapangan.